INTEGRATING OF GEOPHYSICAL AND AGROCHEMICAL METHODS FOR SLOPE LANDS STUDYING - Kruglov, О.; Menshov, О.; Kolada, V.; Achasova, A.; Andreeva, О. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The increasing of the soil degradation of agricultural lands in Ukraine requires the improvement of their survey system. First of all, it is related to the increase of the accuracy of determinations and the density of the measurement grid. To perform these tasks, new methods are involved, primarily the geophysics ones. There are certain advantages of the integration of the studies as well as development of the substantiated rational combination of methods. Recently, promising results of the application of the magnetic susceptibility of soil to characterize the agronomic properties have been obtained. This study shows the results of the integrated application of a number of agrochemical methods and determinations of mass-specific magnetic susceptibility (MS) on the example of podzolized chernozems of Kharkiv district of Kharkiv region. We identified the possibilities of culling of values of soil characteristics from the proceeding of the results of definition of MS. The nature of the correlation between MS and humus content allows us to recommend the replacement of more expensive determination of humus content with cheaper MS. Soil magnetic susceptibility correctly reflects the spatial distribution of the main indicators of eroded lands: the humus content, and physical clay. We propose the study of sloping lands with more optimal techniques of the MS measurement of the soil as the most accessible tool.
Keywords: soil; humus; erosion; integrating; magnetic susceptibility